سورۃ الاحزاب آیت (72) کے تناظر میں امانت و حمل امانت کا مفہوم۔ایک جائزہ: The meaning of The ’Trust which Humanity has undertaken’ in the light of Surah Al-Ahzab, Verse 72 – An Analysis - Hafiz Muhammad Ramzan; Dr Muhammad Atif Aslam Rao (International Research Journal of Arabic and Islamic Studies, 2022)
The Holy Qur'an is a complete code of life. It deals with all aspects of life. However, it is not easy to understand without the interpretation of the Qur'an. Therefore, it is imperative to study exegesis to understand the various conceptions of the Qur'an deeply. This article focuses on 'The Trust which Humanity has undertaken'. The article begins by describing the meaning of 'The Trust which Humanity has undertaken' by various prominent interpreters and references. The article discusses the views of scholars, based on their research that define the meanings and concepts of trust that humanity has undertaken. Furthermore, the paper presents an analytical study from Urdu exegesis regarding the meaning and description of the trust that humanity has undertaken. While interpreting this verse, different interpreters presented different meanings and opinions of the trust. The majority of interpreters' views differ from one another. This article describes how many interpreters have defined the concept of the trust, the different opinions of interpreters, and the nature of the differences. The article concludes itself by elaborating on the best opinion among all.